PROSES PEMBENTUKAN PERATURAN PEMERINTAH PENGGANTI UU DAN PROSES PEMBENTUKAN PERDA - Aulia, Nila; Noor Efendy; Akhmad Zaki Yamani (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
Abstract This journal aims to understand the process of forming government regulations, regulations in lieu of laws and the process of forming PERDA. The method in the journal uses a literature review and the materials used in this journal are several scientific journals, textbooks, research reports, and official documents. The research results state that there are several processes in the formation of government regulations, namely planning a program for compiling government regulations, drafting government regulations, establishing draft government regulations and promulgating government regulations. The preparation of Government Regulations in Lieu of Laws is regulated in Article 52 of Law Number 12 of 2011 concerning the Formation of Legislative Regulations. Meanwhile, the mechanism for drafting regional regulations is divided into 5 stages, namely planning, drafting, discussing, determining/ratifying and promulgating. Key words: Process, Formation, Government Regulation, Substitute for Law, PERDA Abstrak Jurnal ini bertujuan agar dapat memahami tentang proses pembentukan peraturan pemerintah, peraturan pengganti UU dan proses pembentukan PERDA. Metode dalam jurnal menggunakan Review Literatur dan bahan yang digunakan dalam jurnal ini adalah beberapa jurnal ilmiah, buku teks, laporan penelitian, serta dokumen-dokumen resmi. Hasil penelitian menyatakan bahwa ada beberapa proses dalam pembentukan peraturan pemerintah yakni perencanaan program penyusunan peraturan pemerintah, penyusunan rancangan peraturan pemerintah, penetapan rancangan peraturan pemerintah hingga pengundangan peraturan pemerintah. Penyusunan Peraturan Pemerintah Pengganti Undang-Undang diatur dalam Pasal 52 Undang-Undang Nomor 12 Tahun 2011 tentang Pembentukan Peraturan Perundang-Undangan. Sedangkan mekanisme penyusunan peraturan daerah dibagi menjadi 5 tahap, yaitu perencanaan, penyusunan, pembahasan, penetapan/pengesahan dan pengundangan. Kata-kata kunci: Proses, Pembentukan, Peraturan Pemerintah, Pengganti UU, PERDA